1976
DOI: 10.1177/00220345760550033401
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Enamel Solubility by Sodium Monophosphate

Abstract: The preponderance of evidence indicates that sodium monofluorophosphate exerts a highly beneficial effect on dental caries incidence and enamel solubility. Optimal effects are obtained with a concentration of 4 X 10(3) ppm fluoride, by a four-minute application and by adjusting the pH to 4.0. The reaction of sodium monofluorophosphate with enamel is not temperature dependent. Sodium monofluorophosphate is significantly more protective than sodium fluoride in aqueous solutions at all equivalent fluoride concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(6 reference statements)
0
1
1
2
Order By: Relevance
“…It has been suggested that MFP as such may have an anticaries effect by decreasing the acid solubility of enamel (29), by reducing the transport into enamel lesions by plugging the surface layer (30) or by moving more freely into lesions due to less affinity for calcium (4). However, the observation in the present study that MFP was only detectable in clean enamel lesions indicates that MFP is rapidly hydrolyzed in dental plaque.…”
Section: Discussioncontrasting
confidence: 59%
“…It has been suggested that MFP as such may have an anticaries effect by decreasing the acid solubility of enamel (29), by reducing the transport into enamel lesions by plugging the surface layer (30) or by moving more freely into lesions due to less affinity for calcium (4). However, the observation in the present study that MFP was only detectable in clean enamel lesions indicates that MFP is rapidly hydrolyzed in dental plaque.…”
Section: Discussioncontrasting
confidence: 59%
“…The factors that influence the length of the pH-cycling are the fluoride concentration of the de-and remineralizing solutions (22). The findings that the NaMFP toothpaste, which has a definite protective effect, showed less remineralizing efficacy than NaF was not unexpected because pH cycling model consists of only an inorganic solution (24,25). The model choosen to mimic remineralization events is not adequate to estimate the anticaries potential of toothpastes containing NaMFP, because its hydrolysis occurs by phosphatase enzymes, this produced unfavorable results for group C.…”
Section: Discussionmentioning
confidence: 99%
“…Der kariesprotektive Effekt des Fluorids beruht hauptsächlich darauf, dass die Demineralisation der Zahnhartsubstanzen durch kariogene Säuren vermindert und die Remineralisation gefördert wird (Buchalla et al 2002, Casals et al 2007, Feller et al 1976, Limeback 1994). Die lokale, posteruptive Fluoridierung der Zahnhartsubstanzen, z.…”
Section: Abbildungs-undunclassified
“…Dem entgegengesetzt wiesen Attin et al (1996) Anlagerung in das interkristalline Wasser der Schmelzprismen, hervorgerufen wird (Higuchi et al 1974, Klinkenberg und Bibby 1950, Mellberg et al 1966, Stearns 1971, Wefel und Harless 1981. Die antikariogene Wirkung der Fluoride beruht auf der Verminderung der Säurelöslichkeit, der Hemmung der Demineralisation und der Förderung der Remineralisation der Zahnhartsubstanzen (Buchalla et al 2002, Casals et al 2007, Feller et al 1976). Kalzium hat eine hohe Affinität zum Fluorid.…”
Section: Fluoridfreisetzung Aus Füllungsmaterialienunclassified